Irradiated food, consumer concerns and willingness to purchase : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Economics, Massey University, Palmerston North, New Zealand - Bautista, Dennis Malabuyoc (Massey University, 1994)
A national survey of households in New Zealand employed a systematic random sampling technique and conducted to determine the consumers' concern and willingness to purchase irradiated food. The characterization of the consumers based on willingness to pay and level of concern was analyzed using two separate econometric models. The first method used the dichotomous choice logit model for willingness to pay whilst the second model involving four point scaled level of concern employed the ordered logit model. Both models determined the demographic effects on willingness and concern. The consumers level of concern for food irradiation was lower than the consumers' concern for pesticide and chemical residues in food and other food safety issues. The results also suggest that the likelihood of buying irradiated food was dependent on diet, sex, urbanisation, knowledge of food inadiation and consumer beliefs about the radioactivity, wholesomeness and health effects of irradiated food at different levels of significance. Concern was found to be directly effecting willingness to purchase and this concern could influence the consumer's buying behaviour. Concern level, on the other hand, was highly influenced by sex and the consumers knowledge of food irradiation. Higher level of concern was evident among those who were not willing to buy irradiated food. However, a significant number of the surveyed respondents were undecided about buying or not buying irradiated food. The demographic information of this study is useful to the marketing of fresh produce in New Zealand, specially those who anticipate direct marketing activity of irradiated food. The results are also useful in designing policies related to irradiation of food products in New Zealand.
Keywords: Irradiated foods; Food Preservation; New Zealand Consumer behavior; Radiation preservation of food